Acute kidney injury following peripheral angiography and endovascular therapy: A systematic review of the literature. Issue 2 (4th March 2016) - Prasad, Anand; Ortiz‐Lopez, Carolina; Khan, Aazib; Levin, Daniel; Kaye, David M.
Abstract : Introduction: Radiographic contrast administration is a major cause of acute kidney injury (AKI), worldwide. Currently, contrast induced acute kidney injury (CI‐AKI) is the third leading cause of hospital acquired renal failure in the United States. Over 50% of these cases are the result of contrast exposure during cardiac catheterization. The predictive risk factors for and clinical impact of AKI following coronary procedures have been extensively studied and documented in the literature. Similar data, however, are lacking for AKI following angiography or endovascular interventions for lower extremity peripheral artery disease (PAD). Methods: The present review examined the published data available for AKI in patients undergoing peripheral procedures using MEDLINE searches. Specific data on number of peripheral cases, subject characteristics, hydration strategies, and AKI incidence rates was recorded. Results: The systematic review resulted in 50 potentially relevant studies and ultimately 15 studies were selected for detailed analysis that included AKI incidence data on patients undergoing peripheral angiography or interventions. The summated studies included 11, 311 patients and 10, 316 peripheral procedures. The median incidence of AKI in the studies was 10%. The retrieved publications demonstrated significant variations in patient risk factors, definitions of AKI, and specificity of description of endovascular therapies. Conclusions: The incidence, risk factors, and outcomes related to AKI in the context of peripheral angiography or endovascular therapy remain poorly described in the literature and warrant further study in a prospective, systematic fashion. © 2016 Wiley Periodicals, Inc.